Sclerosing Stromal Tumour of Ovary- A Case Report - Joty, Fahmida Sharmin; Dewan, Farhana; Lima, Fahmida Khan; Biswas, Bipul; Nondi, Eva Rani (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Sclerosing stromal tumor (SST) is an extremely rare and distinctive sex cord stromal tumor, which occurs predominantly in the second and third decades of life. Approximately 100 cases reported since first described in 1973. It typically present with pelvic/abdominal pain and tenderness, mass, and/or abnormal menses, and with hormonal activity reported predominantly in postmenarchal females. Only 5 cases of these tumors have been reported in premenarchal girls.We report a case of a 18-year-old girl who developed a sclerosing stromal tumor of ovary and presented with excessive menstruation, pelvic pain and increased frequency of menstruation. Her hormonal status was normal. She was suspected to have a malignant tumor on computed tomography and underwent unilateral salpingo-oopherectomy. It is therefore, necessary to keep in mind the possibility of sclerosing stromal tumor in a young woman Bangladesh J Obstet Gynaecol, 2015; Vol. 30(1) : 56-58